The Influence of Fuel Pump Pressure Variations on the Performance of 2-Stroke Gasoline Direct Injection Engines - Darwin Rio Budi Syaka; I Wayan Sugita; Nugroho Gama Yoga; Muhammad Riangga Widanarko (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa dan Inovasi, 2024)
The direction of technological development in 2-stroke gasoline direct injection engines is to improve engine performance and reduce exhaust gas pollution, where the solution to achieve this is to use a high-pressure electric fuel pump that produces stable fuel pressure and is practical in its application. This research aims to determine the influence of variations in fuel pressure on the performance, especially torque and power, of a 2-stroke gasoline direct injection engine. Tests were carried out on a 110 cc 2-stroke gasoline direct injection motorcycle engine using Research Octane Number (RON) 90 fuel at varying fuel pressures of 7.5 Bar, 8 Bar, and 8.5 Bar on a chassis dynamometer to obtain engine performance data in the form of torque and power. The results of this research show that increasing fuel pressure will increase the atomization of fuel particles so that it will influence increasing the performance of this engine, where maximum torque and power of 6.20 Nm and 2.00 kW are achieved at 3250 rpm, at a pressure of 8.5 Bar.